THE HEALING SPEED OF WOUND INCISION WERE GIVEN AMOXICILLIN AND MEFENAMIC ACID IN WHITE RATS - Lostapa, I Wayan Fandhi Wibawa; Wardhita, Anak Agung Gde Jaya; Pemayun, I Gusti Agung Gde Putra; Sudimartini, Luh Made (Buletin Veteriner Udayana; Vol. 8 No. 2 Agustus 2016, 2016)
The purpose of this research was to know the recovery time of incised wound healing of white rats ( rattus norvegicus) with amoxicillin and mefenamic acid therapy concern in macroscopic and microscopic perspective. The thirty two of male rats in 150-200 gram weight, divided in two random groups with 16 rats contain which are made 2 cm incised wound on linea alba with the depth to penetrate the peritoneum. The first group was given amoxicillin with a dose of 150 mg/kg body weight, whereas the second group was given a combination of amoxicillin with a dose of 150 mg/kg body weight and mefenamic acid with a dose of 45 mg/kg body weight for three days post surgery. The wound healing observed macroscopically every day for 14 days. At day 7 th and day 14 th , 8 rats from each group was euthanized and than the incised wound collected for histopathology examination. The result showed that the combined of amoxicillin and mefenamic acid had faster wound healing than the group which was only given by amoxicillin, where the redish and swelling mark was disappeared on the day 6 th .  The result of histopathologic examination has no significant differences of epitel cell, inflammatory cell, and collagen tissue of the incision wound in the white rats.
Keywords: amoksisilin, asam mefenamat, kesembuhan luka, amoxicillin, mefenamic acid, wound healing